Little fish [videorecording (DVD)] - Tomlin, Mattson; Cooke, Olivia, 1993-; O'Connell, Jack, 1989-; Soko, 1986-; Castillo, Raul; Gabel, Aja (Shout! Factory, 2021)
The film opens amid a global epidemic from Neuroinflammatory Affliction, a severe and rapid Alzheimer's-like condition in which people's memories disappear. Couple Jude Williams and Emma Ryerson are grappling with the realities of NIA, interspersed with glimpses from the past as the two meet and their relationship blooms.